1985
DOI: 10.1093/cvr/19.5.249
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic outflow to the hand in patients with Raynaud's phenomenon

Abstract: Microelectrode recordings of skin nerve sympathetic activity were made in the median nerve supplying the right hand of nine patients with Raynaud's phenomenon and 10 control subjects. With subjects warmed up (finger temperature 33 to 34 degrees C) different manoeuvres were used to evoke strong, single sympathetic bursts, giving rise to vasoconstriction of the same magnitude in patients and control subjects. Immersion of the contralateral hand in ice water for 1 min elicited an increase in sympathetic outflow w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 0 publications
5
19
0
Order By: Relevance
“…Limb immersion in ice water triggers sympathetic vasoconstrictor discharge in the extremities, which reduces cutaneous blood flow (Fagius and Blumberg, 1985) and increases blood pressure in proportion to muscle sympathetic nerve activity (Fagius et al, 1989). The combination of a vasoconstrictive response in the limbs and an increase in facial blood flow is reminiscent of the pattern of vascular response during emotions such as anger and embarrassment (Drummond, 1997;Drummond, 1999), and also resembles the response evoked by microinjections of the synaptic excitant D,L homocysteic acid into the pretentorial part of the lateral periaqueductal gray of decerebrate cats (Carrive and Bandler, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Limb immersion in ice water triggers sympathetic vasoconstrictor discharge in the extremities, which reduces cutaneous blood flow (Fagius and Blumberg, 1985) and increases blood pressure in proportion to muscle sympathetic nerve activity (Fagius et al, 1989). The combination of a vasoconstrictive response in the limbs and an increase in facial blood flow is reminiscent of the pattern of vascular response during emotions such as anger and embarrassment (Drummond, 1997;Drummond, 1999), and also resembles the response evoked by microinjections of the synaptic excitant D,L homocysteic acid into the pretentorial part of the lateral periaqueductal gray of decerebrate cats (Carrive and Bandler, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our study in which muscle sympathetic activity increased only after the first 30 seconds of the CPT, skin sympathetic activity in the median nerve increased immediately upon immersion of the contralateral hand in ice water. 35 This finding is not surprising since skin sympathetic activity is extremely responsive to noxious or arousal stimuli. 23 In contrast, MSNA does not increase and sometimes tends to decrease in response to arousal stimuli.…”
Section: Comparison Of Effects Of Cold Pressor Test On Sympathetic Nementioning
confidence: 92%
“…The discrepancy between their results and our findings of increased MSNA during the CPT mostly likely relate to differences in the duration of the cold stimulus (i.e., a few seconds vs 2 minutes). More recently, Fagius and Blumberg 35 reported that the CPT produced abrupt increases in skin sympathetic activity. In contrast to our study in which muscle sympathetic activity increased only after the first 30 seconds of the CPT, skin sympathetic activity in the median nerve increased immediately upon immersion of the contralateral hand in ice water.…”
Section: Comparison Of Effects Of Cold Pressor Test On Sympathetic Nementioning
confidence: 99%
“…The control group consisted of proposed by Raynaud (1) of increased activity of the 19 healthy volunteers, matched for age and sex. None of the -, i j--j j// ^ A\ subjects, inclüding controls, had taken any vasoactive drug sympathetic System are almost evenly divided (2,3,4). duriBg the previous ten days Seeking clues to the role of the sympathetic System in Informed consent was obtained from all subjects.…”
Section: Introductionmentioning
confidence: 99%